Pembelajaran Bernyanyi Solo Di Kelas 7A SMP Negeri 30 Padang - Reza Pahlevi; Harisnal Hadi (Universitas Negeri Padang, 2023)
The purpose of this study is to be able to identify and describe the implementation of learning arts and culture with Solo Singing material in class 7A SMP Negeri 30 Padang. The type of research used by researchers is qualitative with a descriptive method approach. The research instrument was the researcher himself using tools such as handphones and stationery. Data collection techniques include observation, literature study, interviews, and documentation studies. Data analysis techniques namely classifying data, clarifying data, analyzing data, describing data and concluding. This study found the final result that the lesson plan made by the arts and culture teacher was in accordance with the curriculum used by the school. However, there are still students who do not take part in learning properly because students do not yet have an interest in studying arts and culture subjects, the teaching and learning process is disrupted because there are still students who are noisy in class during learning and there are students who are doing other things outside the context of cultural arts subjects.